2014
DOI: 10.9790/0853-13522931
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of squint presentations in children in a tertiary institution in Western Nigeria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Of particular importance is the fact that majority of the discussants believe that it cannot be treated or corrected, which may explain the low levels of treatment uptake that has been reported in previous studies in Nigeria and Africa as a whole. 3,6,10 Infantile strabismus treatment should take place before the age of 2 years for optimal results, especially regarding stereopsis, which implies that early detection is essential. Thus, the fact that this community, especially women of child-bearing age, do not know that it is treatable will have a negative impact on early detection and treatment in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular importance is the fact that majority of the discussants believe that it cannot be treated or corrected, which may explain the low levels of treatment uptake that has been reported in previous studies in Nigeria and Africa as a whole. 3,6,10 Infantile strabismus treatment should take place before the age of 2 years for optimal results, especially regarding stereopsis, which implies that early detection is essential. Thus, the fact that this community, especially women of child-bearing age, do not know that it is treatable will have a negative impact on early detection and treatment in children.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance is the fact that majority of the discussants believe that it cannot be treated or corrected, which may explain the low levels of treatment uptake that has been reported in previous studies in Nigeria and Africa as a whole. 3,6,10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of importance is the fact that majority of the discussants believe it cannot be treated or corrected, which may explain the underlying cause of poor treatment uptake that has been reported in previous studies in Nigeria and Africa as a whole. 3,6,9 Infantile strabismus treatment should take place before the age of 2 years for optimal result especially regarding stereopsis, which implies that early detection is very essential. Thus, the fact that this community, especially women of child-bearing age, do not know that it is treatable will have a negative impact on early detection and treatment in children.…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based study in Sagamu, Nigeria showed that the uptake of treatment was very low. 9 To address the low uptake of treatment for this condition in developing countries, it is necessary to determine the level of knowledge of the condition within that community. Such information will aid in the planning of an appropriate intervention program.…”
Section: Introductionmentioning
confidence: 99%